Global Economic Prospects and the Developing Countries 1992 - World Bank (Washington, DC: World Bank, 2019)
This year’s report gives special emphasis to international trade in manufactured goods, which have quickly become an important component of developing countries’ exports. Chapter 1 discusses the outlook for the global economy over the next decade, highlights trends in global trading and financial systems, and examines the implications of these trends for developing countries’ growth prospects. Chapter 2 takes stock of the international policy climate and discusses the gains from reductions in industrial countries’ trade barriers. Chapter 3 analyses growing interlinkages in manufacturing and explores their implications for exporters in developing countries.